Biocompatibility of potential wound management products: Hydrogen peroxide generation by fungal chitin/chitosans and their effects on the proliferation of murine L929 fibroblasts in culture - Chung, L.Y.; Schmidt, R.J.; Hamlyn, P.F.; Sagar, B.F.; Andrews, A.M.; Turner, T.D. (1998)
Agaricus bisporus, Fusarium graminearum, Phycomyces blakesleeanus, unbleached and bleached, Rhizomucor miehei, and Rhizopus oryzae were examined as sources of fungal chitin/chitosan. The nitrogen content of the alkali-treated mycelia/sporangiophores obtained after optimization of culture conditions, and of similarly treated A. bisporus stipes, was 2.87, 1.29, 6.27, 6.50, 4.80, and 4.95 w/w, respectively, which relates to an estimated chitin content of 42, 19, 91, 94, 70, and 72, respectively. The hydrogen peroxide (H2O2)-generating ability of the treated fungal materials after 8 h at pH 7.4 and 37 degrees C decreased in the order X. oryzae > P. blakesleeanus unbleached approximate to X. miehi > F. graminearum > A. bisporus > P. blakesleeanus bleached. This did not correlate with estimated chitin content. The effect of these fungal materials on the rate of proliferation of murine L929 fibroblasts in culture also was examined. Both pro-and antiproliferant effects were observed. Significant (P < .05) proproliferant effects were observed on day 6 with R. miehei, R. oryzae, and P. blakesleeanus (unbleached and bleached) at 0.01 w/v. The greatest antiproliferant effect was observed with X. oryzae at 0.05 w/v on day 6 (-63 relative to the control, P < .05; cell viability, 95). fn contrast, A. bisporus failed to affect cell yield significantly at either 0.01 or 0.05 w/v. Addition of catalase to cultures containing X. oryzae or X. miehei at 0.05 w/v failed to abolish the antiproliferant effect on day 3, instead producing a small but significant (P < .05) increase in the effect. Catalase also failed to affect significantly the antiproliferant effect of F, graminearum at 0.05 w/v, but did abolish the proproliferant effect of P. blakesleeanus (unbleached and bleached) on day 3. Overall, our results suggest that the H2O2 being generated by the fungal materials modulates cell proliferation but that this effect is superimposed upon a H2O2-independent antiproliferant effect manifesting itself at the higher concentrations of fungal material. The antiproliferant effect was not attributable to Ca2+, Mg-(2+), or Fe2+ depletion although chelation of Fe2+ did correlate with H2O2-generating ability. Only P, blakesleeanus appears to lack this antiproliferant activity while retaining H2O2-generating activity. These results may aid the selection of fungal chitin/chitosan for further evaluation as a potential wound management material. (C) 1998 John Wiley & Sons, Inc.